Hypoxic Culture (1% O2) Preserves Stemness and Reduces Spontaneous Osteogenic Differentiation In Early and Late Passage Bone Marrow-Derived Mesenchymal Stem Cells - Erreza Rahadiansyah; Muhammad Iqbal Mubarok; Deya Karsari ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2026)
Background: Bone marrow–derived mesenchymal stem cells (BMMSCs) are widely investigated for regenerative medicine applications. During in vitro expansion, BMMSCs may undergo loss of stemness and spontaneous lineage commitment. Hypoxic culture conditions better mimic the physiological bone marrow niche; however, their effects across early and late passages remain incompletely understood. This study aimed to evaluate the effect of hypoxic culture (1% O₂) on stemness-associated features, BMMSC identity, and spontaneous osteogenic mineralization at early and late passages.Methods: BMMSCs were isolated from a New Zealand White rabbit and cultured under normoxic (21% O₂) or hypoxic (1% O₂) conditions. Cells at passages 4 and 8 were analyzed for OCT4, SOX2, and CD105 expression using immunofluorescence and immunocytochemistry. Osteogenic differentiation was assessed by Alizarin Red S staining. Statistical analysis used independent t-tests and Mann–Whitney U tests (p < 0.05).Results: SOX2 and CD105 expression significantly decreased at late passages compared to early passages under both conditions (p < 0.05), whereas OCT4 expression remained stable under hypoxia (p > 0.05). BMMSCs cultured under hypoxia exhibited significantly higher expression of OCT4, SOX2, and CD105 than normoxic cultures at both passages (p < 0.05). Spontaneous calcium deposition was significantly lower under hypoxia (p < 0.05), with no significant difference between early and late passages.Conclusion: Hypoxic culture conditions better preserve stemness-associated features and MSC identity in BMMSCs and suppress spontaneous osteogenic mineralization. Prolonged hypoxic culture supports the maintenance of stem-like characteristics during in vitro expansion, highlighting its relevance for optimizing BMMSC culture strategies.